PENGARUH KOMUNIKASI, BUDAYA ORGANISASI, DAN MOTIVASI TERHADAP KINERJA PERSONEL DI YONBEKANG-5/ PERBEKUD TNI AD - Jarwo Jarwo; Subandijo Subandijo (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2021)
Abstract :The research objective was to obtain fact data and valid and correct and reliable information about the influence of Communication, Organizational Culture and Motivation on Personnel Performance in Yonbekang-5 / Perbekud TNI AD. The research was conducted using a quantitative research approach, using a survey method carried out from March to May 2020, covering pre-survey activities, consolidation, testing instruments through validity, reliability, collection and processing of research data. The research sample is the entire population that is affordable, and has the same characteristics, namely 20 personnel for the validity test and 80 personnel for the research sample, taken in fact, who meet the research requirements. Measurements in the study were carried out by giving the value of each question item from all variables, the measure of the value given in each statement using the